Islam and Local Tradition: Tarup as Islamic Communication Media in Wedding Ceremonies in the Sambas Community - Nurhidayah; Ibrahim (UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
This study analyzes a phenomenon unique to the marriage culture of the Sambas community: the use of the tarup as a place that gathers invited guests, especially men, and serves as a medium of communication about Islam and local traditions. It should be noted that previous researchers have not paid serious attention to the tarup. It turns out that tarup is a medium that plays an important role in Islamic and cultural communication, ensuring that Islam and local traditions do not conflict but are complementary. Therefore, this study aims to review in depth the tradition of the tarup and its function as a medium of communication. This study uses a case study approach with a single instrumental case study type and data collection through documentation, in-depth interviews, and observation. Then, data analysis proceeds through the stages of data condensation, data presentation, and data conclusion/verification. The findings of this study confirm that tarup in the wedding procession of the Muslim community in Sambas is part of Islamic and cultural communication media, such as: the tarup tradition at Muslim weddings in Sambas is inseparable from Malay culture and Islamic teachings. Apart from serving as a place to gather invited guests, especially male guests, tarup also functions as a medium of Islamic and cultural communication. Another fact that I found is that tarup in the culture of the Sambas community is currently used as a platform for political campaigns. I refer to this fact as Islam and traditional living in the community.